Safety profile of Japanese encephalitis vaccines: a comprehensive analysis of vaccine adverse event reports from 1993 to 2025 - Liu, Fujun; Ran, Qibo; Zhang, Huajin; Li, Zhongyu; Chen, Jing (Frontiers in Public Health, 2025)
ObjectivesJapanese encephalitis is a severe mosquito-borne disease requiring effective prevention and ongoing vaccine safety monitoring. This study aimed to analyze the characteristics, severity, and reporting trends of adverse events associated with Japanese encephalitis vaccines (JEV) in the U. S. Vaccine Adverse Event Reporting System (VAERS). We also investigated the correlation between Google search trends and adverse event reporting.MethodsData were extracted from VAERS (1993–2025). Descriptive statistics, including demographics and temporal trends, were performed. Disproportionality analysis used the reporting odds ratio (ROR) with a 95% confidence interval (CI). Google Trends analysis covered 2004–2025 (worldwide, topic: “Japanese Encephalitis Vaccine”).ResultsA total of 1,384 reports (6,596 vaccine-event pairs) were retrieved. IXIARO accounted for 3,452 pairs, JE-VAX 1368, J-VAX 698, and “unspecific Brand” 1,078. Serious reports totaled 284 (20.5%), and fatal reports 11 (0.80%). The 18–29 years group comprised 39.52% (n = 547) of reports, while the ≥60 years group constituted 3.4% (n = 47), with no fatal outcomes reported in this demographic. Key disproportionality signals (RORs) included nausea (n = 134, ROR = 1.32), dizziness (n = 132, ROR = 1.33), pruritus (n = 127, ROR = 2.33), and urticaria (n = 122, ROR = 2.89). Noteworthy brand-specific signals: IXIARO (loss of consciousness n = 32, ROR = 2.88; seizure n = 17, ROR = 2.97), JE-VAX (encephalitis n = 5, ROR = 15.69; angioneurotic oedema n = 4, ROR = 68.17), and J-VAX (laryngospasm n = 11, ROR = 185.73). Google search volume showed strong temporal correlation with VAERS reports (2004–2025).ConclusionThis study revealed the reporting patterns of JEV vaccine adverse events in the VAERS database, indicating that a considerable proportion of reports were serious events, and allergic reactions such as pruritus, rash, and urticaria were prominent. The observed overlap between spontaneous reporting and online search trends suggests public awareness and information dissemination influence reporting patterns. These findings underscore the need for continued JEV safety surveillance and further investigation.